Barikan, Nilai-Nilai Islam dan Integrasi Kehidupan Sosial-Keagamaan: Studi Living Quran dan Hadits - Kirom, Makhiulil (IAIN Ponorogo, 2025)
Barikan has a religious dimension worthy of exploration. It is a Javanese cultural practice that integrates Islamic values such as gratitude, charity, and brotherhood into social life. This tradition reflects the concepts of the Living Quran and Living Hadith, where the teachings of the Quran and the Prophet’s Sunnah are manifested in collective rituals that strengthen social solidarity and religious identity. Using a qualitative approach based on ethnographic methods, this research was conducted through participatory observation and in-depth interviews in a village in East Java where this tradition is practiced. The findings reveal that the Barikan tradition is a medium for praying for ancestors and an educational platform for Islamic values such as gratitude, cooperation, and generosity. In addition to fostering ukhuwwah Islamiyah (Islamic brotherhood), this tradition also functions as a tool for social unification and a reinforcement of local Islamic identity. By uncovering the religious values embedded in the Barikan tradition, this study highlights the importance of cultural and religious acculturation in maintaining social harmony.